Classical macroeconomics: some modern variations and distortions - Ahiakpor, James C. W. (London: Routledge, 2003)
The Great Depression and Keynes's definition of economic concepts made it difficult for modern economists to appreciate the classical insights. This book clarifies the classical explanations to resolve the continuing disputes.
Includes bibliographical references and index
rpm 25/10/13
Loans
Keywords: Macroeconomics